Potential applications of biogenic selenium nanoparticles in alleviating biotic and abiotic stresses in plants: A comprehensive insight on the mechanistic approach and future perspectives - Zohra, Efat; Ikram, Muhammad; Omar, Ahmad A.; Hussain, Mujahid; Satti, Seema Hassan; Raja, Naveed Iqbal; Mashwani, Zia-Ur-Rehman; Ehsan, Maria (Green processing and synthesis, 2021)
In the present era, due to the increasing incidence of environmental stresses worldwide, the developmental growth and production of agriculture crops may be restrained. Selenium nanoparticles (SeNPs) have precedence over other nanoparticles because of the significant role of selenium in activating the defense system of plants. In addition to beneficial microorganisms, the use of biogenic SeNPs is known as an environmentally friendly and ecologically biocompatible approach to enhance crop production by alleviating biotic and abiotic stresses. This review provides the latest development in the green synthesis of SeNPs by using the results of plant secondary metabolites in the biogenesis of nanoparticles of different shapes and sizes with unique morphologies. Unfortunately, green synthesized SeNPs failed to achieve significant attention in the agriculture sector. However, research studies were performed to explore the application potential of plant-based SeNPs in alleviating drought, salinity, heavy metal, heat stresses, and bacterial and fungal diseases in plants. This review also explains the mechanistic actions that the biogenic SeNPs acquire to alleviate biotic and abiotic stresses in plants. In this review article, the future research that needs to use plant-mediated SeNPs under the conditions of abiotic and biotic stresses are also highlighted.